(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
The summary of this work is the research that was conducted for the rehabilitation of paraplegics, stroke and trauma in order to help them rehabilitate the hand without the need for surgeries, as it operates with compressed air, which can be used during the movement of the hand so that smart gloves work to enhance the strength of the hand muscles and movement Joints where the user can handle the device simply without the need for anyone’s help.